Probing new physics in diphoton production with proton tagging at the Large Hadron Collider - Fichet, S.; Von Gersdorff, G. [UNESP]; Kepka, O.; Lenzi, B.; Royon, C.; Saimpert, M. (American Physical Society (APS), 2014)
The sensitivities to anomalous quartic photon couplings at the Large Hadron Collider are estimated using diphoton production via photon fusion. The tagging of the protons proves to be a very powerful tool to suppress the background and unprecedented sensitivities down to 7×10-15GeV-4 are obtained, providing a new window on extra dimensions and strongly interacting composite states in the multi-TeV range. Generic contributions to quartic photon couplings from charged and neutral particles with arbitrary spin are also presented. © 2014 American Physical Society.